Preparation and characterization of albumin nanoparticles encapsulating curcumin intended for the treatment of breast cancer - Jithan, AV; Madhavi, K; M, Madhavi; K, Prabhakar (International Journal of Pharmaceutical Investigation)
Introduction: For the real-time clinical utilization of curcumin (an ayurvedic natural product) to treat breast cancer, its dissolution, rate limited solubility, poor tissue absorption, and extensive in vivo metabolism that leads to its poor systemic bioavailability should be overcome. A polymer-based nanoparticle formulation using bovine serum albumin can increase its aqueous solubility and can achieve protected, sustained, and targeted therapy in breast cancer. Materials and Methods: Desolvation technique was optimized for the preparation of albumin nanoparticles. Particle size, drug release, encapsulation efficiency, drug polymer interaction were the in vitro properties that were determined. Cell culture studies, in vivo pharmacokinetics in rats were used for biological characterization of the formulation. Results: The formulations were successfully prepared using 1:1, 1:2, 1:3, 1:4 drug: polymer ratios and the percent entrapment was found to be 74.76%, 91.01%, 85.36%, 86.42%, respectively, and particle size determined by zetasizer was found to be 225.1, 223.5, 226.3, 228.7 nm, respectively, and in vitro release was sustained for at least one month with drug release of 75.74%, 65.97%, 64.42%, 54%, respectively. The dissolution rate and aqueous solubility of curcumin was enhanced with this formulation. Fourier transform infrared spectroscopy (FTIR) studies demonstrated that the drug was not changed in the formulation during the fabrication process. The proliferation assays in MDA-MB-231 tumor cell lines indicated more effectiveness of the formulation compared to its solution form. In rats, albumin nanoparticles sustained drug release, demonstrated more bioavailability, improved pharmacokinetic properties, and enhanced tissue targetability of the drug. Conclusions: An effective curcumin-albumin nanoparticle formulation was successfully developed using a desolvation technique.
Keywords: Albumin nanoparticles; breast cancer; curcumin; solubility; sustained release